PELATIHAN E-LEARNING DASAR BAGI GURU - Mahendra Adhi Nugroho (Universitas Pahlawan Tuanku Tambusai, 2022)
Teaching and learning activities in the classroom now have many challenges and demands. One of the challenges teachers face is the increasing amount of information that students can access, leaving teachers far behind in updating the information that students access. Therefore, it seems that teachers are forced to balance by looking for additional information using various media such as internet access and the latest reference books. After completing the basic e-learning training with a theoretical and practical approach for high school economics teachers in Yogyakarta, the trainees are expected to be able to compile online e-learning learning materials using the Edmodo platform. The adoption of the Edmodo platform is expected to make teachers not only rely on one learning model using conventional models. Based on the description of the implementation of the training activities, it can be concluded that the participation of the training participants is 90%. Participants actively ask and listen to the material given until the e-learning training ends. Participants hope a similar program will be repeated with other skills training programs. Keywords: Training, e-learning, Edmodo